2019
DOI: 10.1002/esp.4694
|View full text |Cite
|
Sign up to set email alerts
|

The effect of accelerated soil erosion on hillslope morphology

Abstract: Intensive agricultural land use can have detrimental effects on landscape properties, greatly accelerating soil erosion, with consequent fertility loss and reduced agricultural potential. To quantify the effects of such erosional processes on hillslope morphology and gain insight into the underlying dynamics, we use a twofold approach. First, a statistical analysis of topographical features is conducted, with a focus on slope and gradient distributions. The accelerated soil erosion is shown to be fingerprinted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 76 publications
2
18
0
Order By: Relevance
“…Thus, the runoff peak of the convergent hillslopes is smaller in the outlet than the parallel and divergent plans, which also reflects the higher time to concentration (greater discharge time). This could be consistent with the results obtained by Tucker and Bras [47] and Bonetti et al [48] if we consider the differences generated at different scales. According to the results of this study, in all soils with constant RC and different CHs, the highest runoff peak is for divergent hillslopes with straight or concave profiles and the lowest amount for convex-convergent hillslopes.…”
Section: Runoff Peaksupporting
confidence: 93%
“…Thus, the runoff peak of the convergent hillslopes is smaller in the outlet than the parallel and divergent plans, which also reflects the higher time to concentration (greater discharge time). This could be consistent with the results obtained by Tucker and Bras [47] and Bonetti et al [48] if we consider the differences generated at different scales. According to the results of this study, in all soils with constant RC and different CHs, the highest runoff peak is for divergent hillslopes with straight or concave profiles and the lowest amount for convex-convergent hillslopes.…”
Section: Runoff Peaksupporting
confidence: 93%
“…Moreover, recasting the problem in terms of a consistent coupled system of PDEs makes it possible to analyze theoretically the landscape evolution process. As detailed below (Materials and Methods), an analytic solution for the steady-state hillslope profile can be derived (44) and then used as a basic state for a linear stability analysis to identify the critical conditions for the first channel formation and the characteristic valley spacing.…”
Section: Significancementioning
confidence: 99%
“…Even still, there is very much to do. Recent research that points to future work includes that by Dotterweich (2013) who coupled historic written records with geomorphic field evidence to describe landscapes long used and abused by agriculture, and Brecheisen et al (2019) and Bonetti et al (2019) who identified and modelled erosional impacts on landform surface roughness and hillslope morphology based on highresolution LiDAR. But perhaps of most pressing importance is how to address the fact that quantitative understanding about how human forcings are changing soils that can only be described to be elementary (Tugel et al, 2005;Richter and Yaalon, 2012).…”
Section: Some Conclusionmentioning
confidence: 99%
“…() and Bonetti et al. () who identified and modelled erosional impacts on landform surface roughness and hillslope morphology based on high‐resolution LiDAR. But perhaps of most pressing importance is how to address the fact that quantitative understanding about how human forcings are changing soils that can only be described to be elementary ( Tugel et al., ; Richter and Yaalon , ).…”
Section: Some Conclusionmentioning
confidence: 99%